2008
DOI: 10.1016/j.ijrobp.2007.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Steep Dose–Response Relationship for Stage I Non–Small-Cell Lung Cancer Using Hypofractionated High-Dose Irradiation by Real-Time Tumor-Tracking Radiotherapy

Abstract: A steep dose-response curve between 40 and 48 Gy using a daily dose of 12 Gy delivered in one week was identified for stage IB NSCLC in SBRT using RTRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 34 publications
6
82
1
1
Order By: Relevance
“…It is still not certain whether we should use real-time tracking of the prostate markers during the delivery of radiotherapy as RTRT for lung cancers (24), and permit irradiation only when the fiducial markers are within the gating window. Litzenberg et al suggested that 2 of their 11 patients would have benefited from continuous target tracking and threshold-based intervention from their analysis 9 of intra-fraction organ motion (11).…”
Section: Discussionmentioning
confidence: 99%
“…It is still not certain whether we should use real-time tracking of the prostate markers during the delivery of radiotherapy as RTRT for lung cancers (24), and permit irradiation only when the fiducial markers are within the gating window. Litzenberg et al suggested that 2 of their 11 patients would have benefited from continuous target tracking and threshold-based intervention from their analysis 9 of intra-fraction organ motion (11).…”
Section: Discussionmentioning
confidence: 99%
“…Onimaru et al reported that the difference in the local control rate between 40 and 48 Gy in 4 fractions at the isocenter was larger with stage IB than with stage IA [10].…”
Section: Introductionmentioning
confidence: 99%
“…There can be a dose-response relationship between tumor size and the irradiated dose in SBRT [5][6][7][8], and Kestin et al reported that higher doses are associated with better survival for T1-T2N0M0 NSCLC [5]. Guckenberger et al reported that a strong dose-response relationship was observed in NSCLC [6].…”
Section: Introductionmentioning
confidence: 99%